Regulation of the Structure of Zirconium-Based Porphyrinic Metal–Organic Framework as Highly Electrochemiluminescence Sensing Platform for Thrombin - Li, Peipei; Luo, Luo; Cheng, Dan; Sun, Yan; Zhang, Youyu; Liu, Meiling; Yao, Shouzhuo (Analytical chemistry (Washington), 2022)
An electrochemiluminescence (ECL) sensor provides a sensitive and convenient method for early diagnosis of diseases; however, it is still a challenge to develop simple and sensitive sensing platforms based on efficient ECL signals and luminophore groups. Porphyrin-based metal–organic frameworks (MOFs) show great potential in ECL sensing; however, the mechanism and structure–activity relationship, as well as application, are rarely reported. Herein, hydrothermal reactions obtained porphyrin Zr-MOFs (PCN-222) with different specific surface areas, pore sizes, structures, and surface charge states by tuning the reaction time were developed, which served both as the ECL luminophore, coreaction promoter for S2O8 2–, and a connection in the ECL immunoassay. By progressively controlling the condition of the hydrothermal reaction, PCN-222 with large surface area-abundant micropores can be obtained, which has good conductivity and positively charged surfaces, obtaining excellent ECL performance. The ECL performance and the enhancement mechanism were investigated in detail. Using PCN-222-6h with the best ECL intensity as the immobilization matrix for the aptamer, a highly sensitive and selective assay for thrombin was developed. The decrease of the ECL signal was logarithmically linear with the concentration of thrombin in the range from 50 fg mL–1 to 100 pg mL–1 with a low detection limit of 2.48 fg/mL. This proposed strategy provides a brand new approach for tuning of the structures of MOFs as effective ECL signal probes, thus providing wider possibilities for effective ECL immunoassays in the detection of other biomarkers in diagnosis of diseases.